1998
DOI: 10.1002/(sici)1097-0290(19980405)58:1<35::aid-bit4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Examination of protein adsorption in fluidized bed and packed bed columns at different temperatures using frontal chromatographic methods

Abstract: The influences of various experimental parameters on the dynamic adsorption capacity (DAC) and the dynamic adsorption rate (DAR) of a biomimetic affinity silica‐based adsorbent in fluidized and packed bed columns operated under plug flow conditions and at different temperatures have been investigated with different inlet concentrations of hen egg white lysozyme (HEWL) and human serum albumin (HSA). The DACs as well as the DARs of both the fluidized and packed beds were examined at 10% saturation (i.e., at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 36 publications
(61 reference statements)
2
7
0
Order By: Relevance
“…However, higher amount of N protein was eluted with the buffer containing 300 mM imidazole (lanes [12][13][14][15][16], and the thickest band was observed on lane 13 (Fig. 1).…”
Section: Optimization Of Imidazole Concentration In Elution Buffermentioning
confidence: 96%
See 2 more Smart Citations
“…However, higher amount of N protein was eluted with the buffer containing 300 mM imidazole (lanes [12][13][14][15][16], and the thickest band was observed on lane 13 (Fig. 1).…”
Section: Optimization Of Imidazole Concentration In Elution Buffermentioning
confidence: 96%
“…The protein adsorption on IMAC is governed by various factors such as the type of chelating ligand, metal ion, the surrounding chemical environment and experimental parameters on the dynamic binding capacity [11][12][13][14]. Furthermore, Sharma et al [12] demonstrated that the role of ionic strength and pH of the chromatographic medium is significant in governing the binding interaction between the protein and the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments with 50% (v/v) antiserum, the significant drop in MabSelect's Ig binding capacity from 48 to 37 mg mL −1 , that was observed on shifting from ambient to 4-8 • C (Fig. 3), is most likely attributable to reduced mass transfer [34,35] at low temperature combined with an increased tendency for support fouling to occur. It is plausible that the latter effect could, at least in part, account for: (i) MabSelect's further reduction in binding capacity to just 22 mg mL −1 on raising the antiserum strength two-fold (i.e.…”
Section: Dynamic Ig Binding Capacitymentioning
confidence: 98%
“…either the rate of adsorbate-adsorbent interaction or the rate of adsorbate diffusion (pore or film) as controlling the overall adsorption mechanism [1][2][3][4][5]. Arve and Liapis [6] developed a sophisticated model for biospecific affinity chromatography considering three rate controlling mechanisms simultaneously, two for film and porediffusion mass transfer mechanisms and one for the interaction between adsorbate and adsorbent.…”
Section: Introductionmentioning
confidence: 99%